Mothers' experience of caring for home-quarantined children after close contact with COVID-19 in Korea: an exploratory qualitative study - Hyeyeon Lee; Mihui Kim; Ocksim Kim; Sue Kim; Seongmi Choi (Korean Society of Women Health Nursing, 2021)
Purpose The world saw a shift into a new society consequent to the coronavirus disease 2019 (COVID-19), which made home quarantine mandatory for a person in close contact with those who tested positive. For children, however, home quarantine was not limited only to themselves but parents, especially mothers were involved and required to quarantine. This qualitative study aimed to explore and understand mothers' experience and their related psychosocial issues while caring for their school-aged children in Korea, who had to home quarantine after coming in close contact with COVID-19 positive individuals. Methods Data were collected from October 2020 to January 2021 via in-depth, semi-structured interviews with nine mothers of children who had to home quarantine. Interviews were conducted face-to-face in an independent space near the participant's home or workplace (n=5) or via online platforms or telephone (n=4). The data were analyzed using thematic analysis through several iterative team meetings. Results Thematic analysis revealed the following four themes: "Unable to be relieved due to uncertain situations surrounding me," "Blame and hurt toward me, others, and one another," "Pulling myself together for my children in my broken daily life," and "Changes in the meaning of life amid COVID-19." Conclusion The narratives show that mothers experienced psychosocial difficulties while caring for their children during home quarantine. It is necessary to reduce the social stigma toward individuals in home quarantine and establish policies to ensure work-family compatibility for such mothers.